Studies on the differential equations of enzyme kinetics. II. bimolecular reaction: the fitting of experimental data to the simplified model - Claude Marmasse; Joseph Wiener (International Journal of Mathematics and Mathematical Sciences)
Efficient and unbiased estimates of the parameters of the differential system, as well as simultaneous fiducial limits, are obtained through an (eventually weighted) least-squares fitting to a Taylor expansion of the concentration of the products of the reaction.